1997
DOI: 10.1074/jbc.272.9.5814
|View full text |Cite
|
Sign up to set email alerts
|

Increased Uptake and Accumulation of Vitamin C in Human Immunodeficiency Virus 1-infected Hematopoietic Cell Lines

Abstract: Vitamin C (ascorbic acid) is required for normal host defense and functions importantly in cellular redox systems. To define the interrelationship between human immunodeficiency virus (HIV) infection and vitamin C flux at the cellular level, we analyzed vitamin C uptake and its effects on virus production and cellular proliferation in HIV-infected and uninfected human lymphoid, myeloid, and mononuclear phagocyte cell lines. Chronic or acute infection of these cell lines by HIV-1 led to increased expression of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 41 publications
1
23
0
Order By: Relevance
“…Ascorbic acid is known to increase the accessibility and absorption of iron from non-heme iron sources [4]. Vitamin C has been demonstrated to kill HIV-positive cells and help HIV-positive individuals by increasing the immune system [5]. Vitamin C significantly decreases the adverse effect of reactive species such as reactive oxygen and nitrogen that can cause oxidative damage to macromolecules such as lipids, DNA and proteins [6].…”
Section: Introductionmentioning
confidence: 99%
“…Ascorbic acid is known to increase the accessibility and absorption of iron from non-heme iron sources [4]. Vitamin C has been demonstrated to kill HIV-positive cells and help HIV-positive individuals by increasing the immune system [5]. Vitamin C significantly decreases the adverse effect of reactive species such as reactive oxygen and nitrogen that can cause oxidative damage to macromolecules such as lipids, DNA and proteins [6].…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, this difference may be due to that HL60 and U937 cells may express other GLUT transporters and these GLUTs may bind resveratrol with lower affinity. Literature data shows that besides the abundant expression of GLUT1 no reactivity was observed with anti-GLUT2, -GLUT3, -GLUT4, or -GLUT5 antibodies in HL60 (65) or U937 cells (48). However, there are no data regarding the expression of GLUT6 -12 on these cells, so we cannot dismiss the possibility that HL60 or U937 cells express some of these GLUT transporters and that these GLUTs may bind resveratrol with lower affinity.…”
Section: Discussionmentioning
confidence: 79%
“…Short uptake assays enabled us to carry out a detailed kinetic analysis of the transport of 2DG as distinct from the accumulation of the hexose. Both HL-60 and U-937 cell lines express mainly GLUT1 (48,65), and only one saturable component of substrate transport was detected on either cell line, with K m values of 2.5-8.5 mM, as expected from the functional properties of GLUT1 (38,39,65). Resveratrol inhibited glucose transport in both cells, which demonstrated that the deleterious effect of the phytoalexin on glucose uptake could be validated in different human cells, providing convincing evidence that resveratrol affects the functional activity of GLUT1 in a manner independent of the cellular environment in which the transporter is expressed.…”
Section: Discussionmentioning
confidence: 99%
“…upon treatment with large doses of ascorbate (based on bowel tolerance), he noted that vitamin c was more rapidly metabolized depending on the severity of the disease, thus necessitating a higher vitamin c dosage (15). ascorbate has been demonstrated to kill HiV directly in both blood and culture medium (22), and preferentially lessens the viability of HiV-infected cells to reproduce or survive (23). ascorbate has also been shown to improve the clinical status of HiV-infected patients, such as those who develop myopathy secondary to azT therapy (24), and to lower oxidative stress (16).…”
Section: Discussionmentioning
confidence: 99%